An unexpected fungal infection in a patient with leukaemia. Issue 3 (March 1981) - Jameson, B; Carter, R L; Watson, J G; Hay, R J
Abstract : A 58-year-old man, who was entering remission from acute monocytic leukaemia, died unexpectedly after five days of fever. Cultures of necropsy material grew the yeast Trichosporon beigelii, and subsequent histological examination showed a widely disseminated infection. This fungus usually causes a localised lesion of the hair shaft (piedra). Deep-seated infections due to Trichosporon spp. have been recorded infrequently and disseminated infections on only five previous occasions. None of these has been from the United Kingdom. This case report describes some of the difficulties of diagnosis.